Convertible debt and asset substitution of multinational corporations - Batten, Jonathan A.; Khaw, Karren Lee-Hwei; Young, Martin R. (Journal of Corporate Finance, 2021)
Internationalization enables multinational corporations (MNCs) to diversify their sources and types of debt, as well as earnings, although doing so can negatively impact firm risk and the agency costs of debt. Utilizing a primary sample of United States (US) based MNCs compared with domestic corporations (DCs), we find that MNCs are indeed riskier than DCs when considering systematic risk. Further, recognizing the heterogeneity of long-term debt, we find these MNCs consistently maintain a higher convertible debt ratio compared to DCs. We argue this is to mitigate the agency costs related to the asset substitution problem.